Sola Experientia: Suatu Analisis Terhadap Teologi Schleiermacher - Marde Christian Stenly Mawikere (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat)
This article is an overview of the theology of Friedrich Schleiermacher, known as the Father of Modern Theology. By using qualitative research methods on various available literature that review the life and theological thinking of Schleiermacher, the author tries to reveal that the unique thinking of FriedrichSchleiermacher's theology is strongly influenced by his spiritual background, parental influence, church origin and tradition, educational patterns and the thought of his theological education and zeit geist (the spirit of the times) who were carrying the current of modern thought when Schleiermacher lived. On the one hand, Schleiermacher's theology is often considered to be liberal in the theological paradigm of reform and evangelicalism because it departs from feeling, not from the spirit of Sola Scriptura. But on the other hand, Schleiermacher's theology makes a positive contribution because it gives a place to the experience of faith (Sola Experientia) with a living God who can not only be reached with philosophia or wisdom.